2006
DOI: 10.1590/s1678-97412006000300005
|View full text |Cite
|
Sign up to set email alerts
|

<![CDATA[<B>Proportion among the segments of the normal tricuspid valve annulus</B>: <B>parameter for valve annuloplasty</B>]]>

Abstract: Proporção entre os segmentos do anel da valva tricúspide normal: um parâmetro para realização da anuloplastia valvar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Antoniali and colleagues [3] studied 30 normal tricuspid valves from cadavers without fixation and they measured each cuspid. They found that the septal segment of tricuspid valves occupied 29.5% of the ring, while the anteroposterior segment was 70.5%, providing a ratio of 1:2.43.…”
Section: Special Measures To Do De Vega Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Antoniali and colleagues [3] studied 30 normal tricuspid valves from cadavers without fixation and they measured each cuspid. They found that the septal segment of tricuspid valves occupied 29.5% of the ring, while the anteroposterior segment was 70.5%, providing a ratio of 1:2.43.…”
Section: Special Measures To Do De Vega Proceduresmentioning
confidence: 99%
“…There is growing evidence that in patients with a bicuspid aortic valve (BAV), the transvalvular hemodynamics, especially aortic insufficiency, are associated with the AA phenotype and risk of aTAd [3,4]. The patient's age is also important: eg, a 20-year-old man with a 4.5-cm AD is more than 7 z score values apart from his expected age-adjusted, gender-adjusted, and body surface area-adjusted AA diameters, indicating a highly pathologic process!…”
mentioning
confidence: 99%
See 1 more Smart Citation